The psychological impact of the COVID-19 pandemic on Greek teachers and the emerging challenges for their professional development - Raikou, Natassa; Konstantopoulou, Georgia; Lavidas, Konstantinos (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2021)
The present study focuses on the psychological consequences of the pandemic on Greek teachers on anxiety, post-traumatic stress and personal skills. The research was conducted by a Greek university, a few months after the beginning of lockdown and changing the teaching process to distance education. An electronic questionnaire was used as a research tool, which was completed by 213 primary and secondary school teachers in Western Greece. The questionnaire included demographics as well as questions from three questionnaires: State Trait Anxiety Inventory, revised Impact of Event Scale, as well as selected questions from the Personal Skills Inventory. The elaboration of the findings revealed the existence of medium anxiety and low self-esteem for the teachers, as well as an estimation of the factors that increase them. Nevertheless, a discussion on the opportunities emerged for the teachers’ development and the contribution of Adult Education to this direction is ready to start.